HIGH-QUALITY EMPLOYMENT INDEX CONSTRUCTION BY SECOND CLASSROOM EMPOWERMENT: Based On Survey Data From Zhanjiang University Of Science And Technology - Yang, Xiaojuan; Xie, Qinghua (IJBLE Scientific Publications Community Inc., 2022)
The transfer of independent colleges has intensified the competition for talent training among ordinary colleges and universities. The